Multi-access Edge Computing fundamentals, services, enablers and challenges: A complete survey. (March 2022) - Liang, Bin; Gregory, Mark A.; Li, Shuo
Abstract: Traffic over mobile cellular networks has significantly increased over the past decade, and with the introduction of 5G there is a growing focus on throughput capacity, reliability, and low latency to meet the demands of new and innovative applications. Multi-access Edge Computing (MEC) is being developed to achieve a series of challenges posed by the introduction of new applications and services that require ultra-low latency and high bandwidth. This article is a comprehensive survey of recent advances in MEC and provides a description of the MEC concept, framework, and capabilities. We also summarize a set of MEC technology enablers including Software Defined Networking, Network Function Virtualization, Information-Centric Networking, Service Function Chaining, Cloud-Radio Access Networks, Fog-computing based Radio Access Networks and Network Slicing. The MEC use cases and the open research challenges are presented.